KETRAMPILAN KADER SEBAYA DALAM EDUKASI MEMPENGARUHI PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI - Tarsikah Tarsikah; Dessy Amelia; Wahyu Setyaningsih; Ika Yudianti; Nabila Ayu Oktaviani; Dewi Wardha Imania (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2022)
The rapid physical and psychological changes of adolescents bring several consequences, including risky behavior if they do not have a correct understanding of adolescent reproductive health. Peer cadres are one of the potential local resources in the village whose function can be optimized as a source of information. Objective: to increase the knowledge and skills of peer cadres in providing education to adolescents about reproductive health. Methods: the approach used in this service activity is educative and participatory, with a question and answer lecture method, demonstration and practicum through activities carried out offline for 2 times in Kalisongo Dau village, Malang Regency, with 5 peer cadres. The results of the activity: the assessment of the skills of peer cadres was carried out by means of observation when providing education to 20 teenagers, the score was in the good category (79). The knowledge of the audience before being given education by peer cadres was in the poor category (average 46) after education was obtained in the sufficient category (average 67). Conclusion: peer cadres already have good skills in educating and there is an increase in knowledge of the audience after education by peer cadres. The knowledge and skills of peer cadres need to be maintained and improved in a structured and sustainable manner in order to optimize their role as a source of information on adolescent reproductive health